2007
DOI: 10.1002/yea.1552
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of Trp mutants isolated as 5‐fluoroanthranilate‐resistant clones in Saccharomyces bayanus, S. mikatae and S. paradoxus

Abstract: Abstract5-Fluoroanthranilic acid (FAA)-resistant mutants were selected in homothallic diploids of three Saccharomyces species, taking care to isolate mutants of independent origin. Mutations were assigned to complementation groups by interspecific complementation with S. cerevisiae tester strains. In all three species, trp3, trp4 and trp5 mutants were recovered. trp1 mutants were also recovered if the selection was imposed on a haploid strain. Thus, FAA selection may be more generally applicable than was previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The two species can make interspecific hybrids, allowing complementation tests with S. cerevisiae alleles. However, with a few exceptions (Serra et al 2003; Talarek et al 2004; Jones et al 2008; Zill and Rine 2008; Gallagher et al 2009; Zill et al 2010), little experimental work has been performed in S. bayanus and even less at genome scale (Bullard et al 2010; Tsankov et al 2010; Busby et al 2011; Guan et al 2011; Muller and Nieduszynski 2012). …”
mentioning
confidence: 99%
“…The two species can make interspecific hybrids, allowing complementation tests with S. cerevisiae alleles. However, with a few exceptions (Serra et al 2003; Talarek et al 2004; Jones et al 2008; Zill and Rine 2008; Gallagher et al 2009; Zill et al 2010), little experimental work has been performed in S. bayanus and even less at genome scale (Bullard et al 2010; Tsankov et al 2010; Busby et al 2011; Guan et al 2011; Muller and Nieduszynski 2012). …”
mentioning
confidence: 99%
“…It is therefore highly likely that the FAA‐resistant and Trp − auxotrophic colonies might be derived from additional mutation(s) of H. polymorpha TRP3, TRP4 or TRP5, which could also confer resistance to 5‐FAA in the tryptophan biosynthetic pathway (Toyn et al , 2000). Similarly, a recent study reported that, among Trp − and FAA‐resistant mutants of diploid and/or haploid Saccharomyces ‐related species, trp3, trp4 and trp5 mutants were recovered; in contrast, no trp1 mutants were recovered by complementation test (Jones et al , 2008). Thus, recycling of the HpTRP1 gene appears impractical for multiple disruptions in H. polymorpha as opposed to S. cerevisiae and Y. lipolytica .…”
Section: Resultsmentioning
confidence: 84%
“…This compound, toxic for prototrophic cells, permits in most cases an easy counterselection of ura3 or ura5 genotypes from a randomly mutagenized population. In the same way, recent advances have demonstrated the potential of 5-fluoroanthranilate for counter-selection of trp1, trp3, trp4 or trp5 genotypes in yeast (Toyn et al, 2000;Cheon et al, 2003Cheon et al, , 2009Lebel et al, 2006;Jones et al, 2008).…”
Section: Dominant Selection Markersmentioning
confidence: 88%